Antiinflammatory Activity of Pagoda Flower (Clerodendrum Paniculatum L.) Ethanol Extract Using Paw Edema Method - Hafiz, Ihsanul; Ginting, Mandike (Asian Journal of Pharmaceutical Research and Development, 2019)
Objectives: The purpose of this study was to determine antiinflammatory activity of pagoda flower (Clerodendrum paniculatum L.) ethanolic extract Design: This study uses an experimental laboratory design. This research uses paw edema method by inducing carrageenin in the legs of male white rats as an induction of inflammation. Interventions: The sample used was pagoda flower ethanol extract in various dosages of 25, 50 and 100 mg / kg. As a comparison, acetosal dose 33 mg / kg was used. Na CMC suspension was used as a negative control. Main outcome measure: The results in this study are the difference in the volume of edema volume from rat feet per unit time. The measurement of the rat's leg volume was measured at 30, 60, 120, 180, 240 and 300 minutes. Conclusion: Pagoda flower ethanol extract does not have good anti-inflammatory activity. there were no significant differences between groups except at dose 100 and positive control at minute 300 of negative control.